Ternary positive electrode material precursor and preparation method thereof, ternary positive electrode material, lithium ion battery, positive electrode, electrical equipment

A three-layered lithium-ion battery positive pole material precursor with a core, intermediate, and shell structure addresses the issues of high diffusion resistance and instability in conventional nickel-based precursors, enhancing lithium-ion transport and structural stability to improve battery performance and longevity.

JP7625700B2Active Publication Date: 2025-02-03CNGR ADVANCED MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023532305
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-27
Filing Date
2022-06-14
Publication Date
2025-02-03
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

Conventional lithium-ion battery positive electrodes made from nickel-based precursors have a dense structure with uneven fragment distribution, leading to high lithium-ion diffusion resistance, poor rate performance, and instability, which results in reduced cycle life and capacity due to cracking of granules.

Method used

A three-layered positive pole material precursor is developed with a core layer, two intermediate layers, and a shell layer, featuring increasing porosity from the core to the shell, which enhances lithium-ion transport channels and structural stability by forming a dense interior with a porous shell.

Benefits of technology

The new structure reduces lithium-ion diffusion resistance, improves charging and discharge performance, extends battery life, and maintains capacity through enhanced structural stability and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625700000003
    Figure 0007625700000003
  • Figure 0007625700000004
    Figure 0007625700000004
  • Figure 0007625700000005
    Figure 0007625700000005
Patent Text Reader

Abstract

The present application provides a ternary positive electrode material precursor and a preparation method thereof, a ternary positive electrode material, a lithium ion battery, a positive electrode, and an electrical device. The ternary positive electrode material precursor includes, from the inside to the outside, a core layer, a first intermediate layer, a second intermediate layer, and a shell layer, in which the porosity of the core layer, the first intermediate layer, and the second intermediate layer increases in order, and the shell layer is the layer with the smallest porosity or is a non-porous layer. The preparation method includes a step of performing a first reaction on a raw material containing a nickel-cobalt-manganese ternary mixed solution, a complexing agent, and a pH adjuster to obtain a core layer, a step of performing a second reaction by adjusting the reaction conditions to form a first intermediate layer on the surface of the core layer, a step of performing a third reaction by adjusting the reaction conditions to form a second intermediate layer on the surface of the first intermediate layer, and a step of performing a fourth reaction by adjusting the reaction conditions to form a shell layer on the surface of the second intermediate layer. The ternary positive electrode material includes, from the inside to the outside, a layer A, a layer B, a layer C, and a layer D. The ternary positive electrode material precursor according to the present application has excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of lithium ion batteries, and in particular to a ternary positive electrode material precursor and a preparation method thereof, a ternary positive electrode material, a lithium ion battery, a positive electrode, and an electrical device.

[0002] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority based on a Chinese application filed with the China Patent Office on January 27, 2022, bearing application number 202210101448.7 and entitled "Ternary positive electrode material precursor and preparation method thereof, ternary positive electrode material, lithium ion battery, positive electrode, and electrical equipment," the entire contents of which are incorporated herein by reference. [Background technology]

[0003] In 2021, China declared that it would aim to peak its carbon dioxide emissions by 2030 and achieve carbon neutrality by 2060. However, the automobile industry is developing rapidly around the world, and the amount of automobile exhaust gas directly affects carbon dioxide emissions. Therefore, green new energy vehicles have become the future development direction of the industry, and lithium batteries are the main power source of new energy vehicles. As the most important component of lithium batteries, positive electrode precursor materials have always been the focus of technology. Currently, the ternary precursors of the 5 series and 6 series, which are most commonly available on the market, have relatively low electrical capacity, which limits their application in new energy vehicles.

[0004] Each precursor manufacturer has developed high nickel precursor products to increase the capacity of the battery and extend the duration of the battery. High nickel large granular precursors are generally prepared by batch method and have a very narrow particle size distribution, resulting in a uniform granular structure.

[0005] Currently, in the field of ternary precursors for lithium batteries, the internal structure of ternary precursor granules is generally a dense structure with few voids and non-uniform void distribution, and the batteries manufactured using such ternary precursor granules have a single diffusion path for lithium ions, a large diffusion resistance of lithium ions, and insufficient rate performance. Furthermore, since the battery is constantly charged and discharged, if the structural strength of the granules is unstable, the granules are likely to crack, which results in a shortened lifespan, a low capacity, and poor safety during use of the lithium secondary battery.

[0006] For this reason, it is urgent to resolve the technical problems of the ternary precursor granules having a uniform internal structure, high diffusion resistance, and cracks due to unstable granule strength, which results in poor battery cycle performance, rate performance, and safety. Summary of the Invention

[0007] The present application aims to provide a ternary positive electrode material precursor and a preparation method thereof, a ternary positive electrode material, a lithium ion battery, a positive electrode, and an electrical device, which can solve the above problems.

[0008] To achieve the above objectives, the present application adopts the following technical solutions:

[0009] The ternary positive electrode material precursor includes, from inside to outside, a core layer, a first intermediate layer, a second intermediate layer, and a shell layer, the core layer, the first intermediate layer, and the second intermediate layer having increasing porosity in this order, and the shell layer is the layer with the smallest porosity or is a non-porous layer.

[0010] Preferably, the porosity of the core layer is 1.40% to 7.96%, the porosity of the first intermediate layer is 2.10% to 8.37%, the porosity of the second intermediate layer is 4.57% to 16.72%, and the porosity of the shell layer is 1% or less, and preferably, the porosity of the core layer is 2.0% to 4.0%, the porosity of the first intermediate layer is 3.0% to 5.0%, the porosity of the second intermediate layer is 7.35% to 10.32%, and the porosity of the shell layer is 0.5% or less.

[0011] Preferably, the average thickness of each of the individual layers of the ternary positive electrode material precursor is 3 μm or less, and preferably, the diameter of the core layer is 1.0 μm to 3.0 μm, the average thickness of the first intermediate layer is 0.2 μm to 2.0 μm, the average thickness of the second intermediate layer is 1 μm to 2.5 μm, and the average thickness of the shell layer is 0.5 μm to 1.5 μm.

[0012] Preferably, the primary granules in the ternary positive electrode material precursor are distributed in a sparsely intersecting needle shape from the inside to the outside along a radial direction of the ternary positive electrode material precursor, preferably the core layer is spherical as a whole, and preferably the primary granules in the shell layer are needle-shaped along a radial direction of the ternary positive electrode material precursor.

[0013] Preferably, the average particle size of the ternary positive electrode material precursor is 12 μm to 15 μm, preferably, D95 / D50=1.0 to 1.6 is satisfied, and preferably, the BET of the ternary positive electrode material precursor is 11 m 2 / g~17m 2 / g.

[0014] Preferably, the half-width α of the 001 peak within the diffraction angle 2θ range of 19.2±1° is 0.6 or less, preferably the half-width α is 0.43 to 0.53, preferably the half-width β of the 101 peak within the diffraction angle 2θ range of 38.5±1° is 0.7 or less, preferably the half-width β is 0.48 to 0.58, preferably the ratio of the half-width β to the half-width α is 1.02 or more, and the peak intensity ratio I001 / I101) is 1.0 to 1.2, preferably the ratio of the half-width β to the half-width α is 1.02 to 1.25.

[0015] Preferably, the general formula of the ternary positive electrode material precursor is Ni x Co y Mn z (OH)2, where 0.8≦x≦0.98, 0.01≦y<0.18, 0.01≦z<0.17, and x+y+z=1.

[0016] The present application further provides a method for preparing the ternary positive electrode material precursor, which includes the steps of: performing a first reaction on a raw material containing a nickel-cobalt-manganese ternary mixed solution, a complexing agent, and a pH adjuster to obtain a core layer; adjusting reaction conditions to perform a second reaction to form a first intermediate layer on the surface of the core layer; adjusting reaction conditions to perform a third reaction to form a second intermediate layer on the surface of the first intermediate layer; and adjusting reaction conditions to perform a fourth reaction to form a shell layer on the surface of the second intermediate layer.

[0017] Preferably, the first reaction, the second reaction, the third reaction, and the fourth reaction are all carried out under stirring, with the stirring speed decreasing in that order, and preferably, the stirring speed for the first reaction is 200 r / min to 240 r / min, the stirring speed for the second reaction is 180 r / min to 230 r / min, the stirring speed for the third reaction is 100 r / min to 200 r / min, and the stirring speed for the fourth reaction is 40 r / min to 100 r / min.

[0018] Preferably, in the first reaction, the second reaction, the third reaction, and the fourth reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution increases in order, preferably, in the first reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 80L / h to 550L / h, in the second reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 150L / h to 650L / h, and in the third reaction and the fourth reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 150L / h to 750L / h, preferably, in each of the first reaction, the second reaction, the third reaction, and the fourth reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution increases stepwise, preferably, the stepwise increase rate is 10% to 100%.

[0019] Preferably, in the first reaction, the second reaction, and the third reaction, the pH of the system gradually decreases, and in the fourth reaction, the pH of the system is higher than that of the third reaction. Preferably, in the first reaction, the second reaction, the third reaction, and the fourth reaction, the pH of the system ranges from 10 to 12.

[0020] Preferably, in the fourth reaction, the pH of the system is 0.10 to 0.30 higher than that of the third reaction system.

[0021] Preferably, the concentration of the nickel-cobalt-manganese ternary mixed solution is 90-130 g / L, preferably, the complexing agent includes one or more of ammonia water, EDTA, ethylenediamine, sodium citrate and urea, preferably, the complexing agent is ammonia water having a mass fraction of 15%-35%, preferably, in the first reaction, the second reaction, the third reaction and the fourth reaction, the concentration of the ammonia water in the system is 2.5 g / L-6.5 g / L, preferably, in the third reaction and the fourth reaction, the concentration of the ammonia water in the system is 1.0-3.0 g / L higher than the concentration of the ammonia water in the second reaction, preferably, the pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, sodium hydrogen carbonate and sodium carbonate, preferably, the pH adjuster is an aqueous sodium hydroxide solution having a mass fraction of 25%-50%.

[0022] The present application further provides a ternary positive electrode material, which includes, from inside to outside, an A layer, a B layer, a C layer, and a D layer, the A layer, the B layer, and the C layer having increasing porosity, the D layer having the smallest porosity or being a non-porous layer, and preferably, the ternary positive electrode material is prepared by sintering the above-mentioned ternary positive electrode material precursor.

[0023] The present application further provides a lithium ion battery cathode comprising the ternary cathode material.

[0024] The present application further provides a lithium ion battery comprising the lithium ion battery positive electrode.

[0025] The present application further provides an electrical device comprising a lithium-ion battery.

[0026] Compared with the prior art, the present application has the following beneficial effects:

[0027] The ternary positive electrode material precursor according to the present application, compared to the conventional ternary precursor having a dense internal structure, includes a core layer, a first intermediate layer, a second intermediate layer, and a shell layer from the inside to the outside, the porosity of the core layer, the first intermediate layer, and the second intermediate layer increases in order, and the shell layer is the layer with the smallest porosity or is a non-porous layer. The porosity of the three internal layers increases in order, and this structure forms a relatively large number of diffusion paths, increases the number of lithium ion transport channels, and reduces the diffusion resistance of lithium ions, effectively increasing the diffusion rate of lithium ions, thereby improving the charge / discharge performance, rate performance, and cycle performance. The shell layer is the layer with the smallest porosity or a non-porous layer, and is formed as a dense shell structure with few pores. Therefore, the ternary positive electrode material precursor is formed in a form with a sparse internal structure and a dense external structure, and can withstand the stress generated by charge / discharge, and the dense shell with few pores can ensure structural stability. Furthermore, the ternary positive electrode material precursor has a porosity in the internal structure that falls within a specific range, and the shell layer is formed as a dense structure with few pores, which improves the strength of the granules and makes them less likely to crack during the charge and discharge process of the battery. As a result, the battery has an improved capacity retention rate after cycling, an extended service life, and excellent battery performance.

[0028] The preparation method of the ternary positive electrode material precursor according to the present application can reliably prepare the above-mentioned ternary positive electrode material precursor having a special four-layer structure by a solution co-precipitation method through the first reaction, the second reaction, the third reaction and the fourth reaction, and the cost is low and the process is stable.

[0029] The ternary positive electrode material, lithium ion battery positive electrode, and lithium ion battery according to the present application have excellent electrical performance, long service life, and high safety and stability. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is a schematic diagram of a ternary positive electrode material precursor according to the present application. [Diagram 2] 1 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Example 1. [Diagram 3] 1 is a high-magnification scanning electron microscope photograph of a ternary positive electrode material precursor obtained in Example 1. [Figure 4] 1 is a high-magnification scanning electron microscope photograph showing a part of a ternary positive electrode material precursor obtained in Example 1. [Diagram 5] 1 is a high-magnification scanning electron microscope photograph of a ternary positive electrode material precursor obtained in Example 2. [Figure 6] 4 is a high-magnification scanning electron microscope photograph showing a part of a ternary positive electrode material precursor obtained in Example 2. [Figure 7] 1 shows XRD spectra of ternary positive electrode material precursors obtained in Examples 1, 2, 3, and 4, respectively. [Figure 8] 1 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Example 2. [Figure 9] 1 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Example 3. [Figure 10] 1 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Example 4. [Figure 11] 2 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Comparative Example 1. [Figure 12] 2 is a high-magnification scanning electron microscope photograph of a ternary positive electrode material precursor obtained in Comparative Example 1. [Figure 13] 1 is a high-magnification scanning electron microscope photograph showing a part of a ternary positive electrode material precursor obtained in Comparative Example 1. [Figure 14]1 is an XRD spectrum of a ternary positive electrode material precursor obtained in Comparative Example 1. [Figure 15] 1 is a SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Comparative Example 2. [Figure 16] 1 is an XRD spectrum of a ternary positive electrode material precursor obtained in Comparative Example 2. [Figure 17] 1 is an SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Comparative Example 3. [Figure 18] 1 is an XRD spectrum of a ternary positive electrode material precursor obtained in Comparative Example 3. [Figure 19] 1 is an SEM photograph of a cross section of a ternary positive electrode material precursor obtained in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings necessary for describing the embodiments are briefly described below, which are merely for illustrating some embodiments of the present application and are not intended to limit the scope of the present application.

[0032] The terms used in this specification should be understood as follows.

[0033] "Prepared by" has the same meaning as "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to be non-exclusive inclusive. For example, a composition, step, method, product, or apparatus that includes recited elements may include not only those elements, but also other elements not specified or inherent in those compositions, steps, methods, products, or apparatus.

[0034] The phrase "consisting of" excludes any unspecified element, step, or composition. When used in the claims, the phrase is closed-form and means that the content is free of materials other than those recited, except for common impurities of interest. When the phrase "consisting of" appears in a clause of claim content rather than in the subject matter of the claim, it limits only the elements recited in that clause and does not exclude other elements from the claim as a whole.

[0035] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of preferred upper and lower limits, it is to be understood that all ranges combining any upper or preferred value of any range with any lower or preferred value of any range, whether or not there is a separate disclosure, are specifically disclosed. For example, if a range of "1-5" is disclosed, it should be understood that the described range includes ranges such as "1-4," "1-3," "1-2," "1-2 and 4-5," "1-3 and 5," etc. Numerical ranges described herein include the critical values ​​and all integers and fractions within the range, unless otherwise indicated.

[0036] In these examples, parts and percentages are calculated by weight unless otherwise specified.

[0037] "Parts by mass" is a basic unit of measurement that expresses the mass ratio relationship of multiple components, and 1 part can represent any unit mass, for example, 1 g or 2.689 g. When the parts by mass of component A are a parts and the parts by mass of component B are b parts, it represents that the ratio of the mass of component A to the mass of component B is a:b, or that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number that represents a multiplication factor). Note that, unlike %, the total parts by mass of all components does not necessarily equal 100 parts.

[0038] "And / or" indicates that at least one of the stated circumstances occurs. For example, A and / or B includes "A and B" as well as "A or B."

[0039] As shown in FIG. 1, the ternary positive electrode material precursor according to the present application includes, from inside to outside, a core layer (core a), a first intermediate layer (porous second layer b), a second intermediate layer (porous third layer c), and a shell layer (shell layer d), the core layer, the first intermediate layer, and the second intermediate layer have increasing porosity in this order, and the shell layer is the layer with the smallest porosity or is a non-porous layer.

[0040] As shown in Figure 1, the first intermediate layer is formed outside the core layer and covers the core layer, the second intermediate layer is formed outside the first intermediate layer and covers the first intermediate layer and the core layer, and the shell layer is formed on the outermost side and covers the second intermediate layer and the first intermediate layer and the core layer covered by the second intermediate layer.

[0041] In one optional embodiment, the porosity of the core layer is 1.40% to 7.96%, the porosity of the first intermediate layer is 2.10% to 8.37%, the porosity of the second intermediate layer is 4.57% to 16.72%, and the porosity of the shell layer is 1% or less.

[0042] In one optional embodiment, the porosity of the core layer is 2.0% to 4.0%, the porosity of the first intermediate layer is 3.0% to 5.0%, the porosity of the second intermediate layer is 7.35% to 10.32%, and the porosity of the shell layer is 0.5% or less.

[0043] In order to evaluate the porosity, in this application, the void area and cross-sectional area of ​​each region are directly obtained using image analysis software (ImageJ), and the porosity of different regions is calculated by the formula "void area = void area of ​​each region / cross-sectional area of ​​each region × 100%". All porosities mentioned in this specification are evaluated by this method.

[0044] The ternary positive electrode material precursor is arranged so that the porosity of the three inner layers increases in order and falls within the above porosity range, and this structure forms a relatively large number of diffusion paths, increases the number of lithium ion transport channels, and reduces the diffusion resistance of lithium ions, effectively increasing the diffusion rate of lithium ions, thereby improving the charge / discharge performance, rate performance, and cycle performance. The shell layer is the layer with the smallest porosity or a non-porous layer, and is formed as a dense shell structure with few holes. Therefore, the ternary positive electrode material precursor is formed in a form in which the inside is sparse and the outside is dense, and can withstand the stress generated by charge / discharge, and the dense shell with few holes can ensure structural stability. The porosity of the internal structure of the positive electrode material ternary precursor falls within a specific range, and the shell layer is formed as a dense structure with few holes, so that the strength of the granules is improved and the granules are less likely to break during the charge / discharge process of the battery, and therefore the battery has improved capacity retention after cycling, extended service life, and excellent battery performance.

[0045] Optionally, the porosity of the core layer is 1.40%, 2%, 3%, 4%, 5%, 6%, 7%, 7.96%, or any value in the range of 1.40% to 7.96%, the porosity of the first intermediate layer is 2.10%, 3%, 4%, 5%, 6%, 7%, 8%, 8.37%, or any value in the range of 2.10% to 8.37%, and the porosity of the second intermediate layer is 4.57%. , 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 16.72%, or any value in the range of 4.57% to 16.72%, and the porosity of the shell layer is 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any value equal to or less than 1%.

[0046] In one alternative embodiment, the average thickness of each of the individual layers of the ternary positive electrode material precursor is 3 μm or less.

[0047] In one optional embodiment, the diameter of the core layer is 1.0 μm to 3.0 μm, the average thickness of the first intermediate layer is 0.2 μm to 2.0 μm, the average thickness of the second intermediate layer is 1 μm to 2.5 μm, and the average thickness of the shell layer is 0.5 μm to 1.5 μm.

[0048] Optionally, the diameter of the core layer is 1.0 μm, 1.5 μm, 2 μm, 2.5 μm, 3.0 μm, or any value in the range of 1.0 μm to 3.0 μm; the average thickness of the first intermediate layer is 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2.0 μm, or any value in the range of 0.2 μm to 2.0 μm; the average thickness of the second intermediate layer is 1 μm, 1.5 μm, 2 μm, 2.5 μm, or any value in the range of 1 μm to 2.5 μm; and the average thickness of the shell layer is 0.5 μm, 1 μm, 1.5 μm, or any value in the range of 0.5 μm to 1.5 μm.

[0049] The average internal thickness of the granules is specified based on the particle size at the end of each reaction step above.

[0050] In one alternative embodiment, the primary granules in the ternary positive electrode material precursor are distributed in a sparse, intersecting needle shape from the inside to the outside along the radial direction of the ternary positive electrode material precursor.

[0051] In one alternative embodiment, the core layer has a generally spherical shape.

[0052] In one alternative embodiment, the primary granules in the shell layer are acicular along the radial direction of the ternary positive electrode material precursor.

[0053] In one alternative embodiment, the ternary positive electrode material precursor has an average particle size of 12 μm to 15 μm.

[0054] In one alternative embodiment, D95 / D50=1.0 to 1.6 is satisfied.

[0055] Optionally, the D95 / D50 of the ternary cathode material precursor is 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or any value in the range of 1 to 1.6.

[0056] The ternary positive electrode material precursor exhibits a narrow particle size distribution, the granules are uniformly distributed, and the electrical performance is better.

[0057] When the ternary positive electrode material precursor granules satisfy the above-mentioned granule size range and particle size distribution, the primary granules are sparsely intersecting needle-like and uniformly distributed, and when used in a battery as a positive electrode material, the diffusion resistance of lithium ions can be reduced and the lithium ions can be transported to a certain extent.

[0058] In one alternative embodiment, the ternary positive electrode material precursor has a BET (specific surface area) of 11 m 2 / g~17m 2 / g.

[0059] Optionally, the BET of the ternary cathode material precursor is 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, or 11m 2 / g~17m 2 / g.

[0060] In one alternative embodiment, the half-width α of the 001 peak in the diffraction angle 2θ range of 19.2±1° is 0.6 or less.

[0061] In one optional embodiment, the half width α is 0.43 to 0.53.

[0062] Optionally, the half-width α is 0.3, 0.4, 0.43, 0.5, 0.6, or any value less than or equal to 0.6.

[0063] In an alternative embodiment, the half-width β of the 101 peak in the diffraction angle 2θ range of 38.5±1° is 0.7 or less.

[0064] In one optional embodiment, the half width β is 0.48 to 0.58.

[0065] Optionally, the half-width β is 0.3, 0.4, 0.48, 0.5, 0.58, 0.6, 0.7, or any value less than or equal to 0.7.

[0066] In one optional embodiment, the ratio of the half width β to the half width α is 1.02 or more, and the peak intensity ratio I(001 / 101) is 1.0 to 1.2.

[0067] In one optional embodiment, the ratio of the half width β to the half width α is 1.02 to 1.25.

[0068] Optionally, the ratio of the half width β to the half width α is 1.02, 1.1, 1.2, 1.25, or any value within the range of 1.0 to 1.25.

[0069] The 001 crystal plane has a relatively small half-width and a high peak intensity, and the granules are preferentially grown along the 001 crystal plane. The crystallinity of the 001 crystal plane is relatively high, and the growth of the primary granules is influenced by this, and the active material precursor prepared in this manner has excellent structural stability. The 001 peak intensity of the precursor material is greater than the 101 peak intensity, and the crystallinity of the granules is superior at the 001 peak. When the positive electrode active material is formed from the precursor material, by combining it with the void distribution of the internal structure, excellent output characteristics, cycle performance, and rate performance can be obtained, and the capacity of the battery can be improved.

[0070] In an alternative embodiment, the general formula of the ternary cathode material precursor is: x Co y Mn z (OH)2, where 0.8≦x≦0.98, 0.01≦y<0.18, 0.01≦z<0.17, and x+y+z=1.

[0071] The present application further provides a method for preparing the above ternary positive electrode material precursor, the method comprising: A step of performing a first reaction on a raw material including a nickel-cobalt-manganese ternary mixed solution, a complexing agent, and a pH adjuster to obtain a core layer; adjusting reaction conditions to carry out a second reaction to form a first intermediate layer on the surface of the core layer; adjusting reaction conditions to carry out a third reaction to form a second intermediate layer on the surface of the first intermediate layer; and adjusting reaction conditions to carry out a fourth reaction to form a shell layer on the surface of the second intermediate layer.

[0072] In an alternative embodiment, the first reaction, the second reaction, the third reaction, and the fourth reaction are all carried out under stirring, and the stirring speed is sequentially decreased.

[0073] In one optional embodiment, the stirring speed of the first reaction is 200 r / min to 240 r / min, the stirring speed of the second reaction is 180 r / min to 230 r / min, the stirring speed of the third reaction is 100 r / min to 200 r / min, and the stirring speed of the fourth reaction is 40 r / min to 100 r / min.

[0074] Reducing the stirring intensity and the degree of supersaturation of the solution in the fourth reaction can contribute to the growth of crystals at the interface, and increasing the pH of the system in the fourth reaction can contribute to the stabilization of the strength of the crystal granules, thus forming a dense shell structure and improving the structural stability.

[0075] The average internal thickness of the granules is determined based on the particle size at the end of each reaction step above.

[0076] Optionally, the stirring speed of the first reaction is 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, or any value in the range of 200 r / min to 240 r / min, the stirring speed of the second reaction is 180 r / min, 190 r / min, 200 r / min, 210 r / min, 220 r / min, 230 r / min, or any value in the range of 180 r / min to 230 r / min, and the stirring speed of the third reaction is 100 r / min, 110 r / min, The stirring speed of the fourth reaction is 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min, 100 r / min, or any value in the range of 40 r / min to 100 r / min, and the stirring speed of the fourth reaction is 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min, 100 r / min, or any value in the range of 40 r / min to 100 r / min.

[0077] In one alternative embodiment, the flow rates of the nickel-cobalt-manganese ternary mixed solution increase in the order of the first reaction, the second reaction, the third reaction, and the fourth reaction.

[0078] In one alternative embodiment, in the first reaction, the nickel-cobalt-manganese ternary mixed solution is added at a flow rate of 80 L / h to 550 L / h, in the second reaction, the nickel-cobalt-manganese ternary mixed solution is added at a flow rate of 150 L / h to 650 L / h, and in the third reaction and the fourth reaction, the nickel-cobalt-manganese ternary mixed solution is added at a flow rate of 150 L / h to 750 L / h.

[0079] Optionally, in the first reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 80L / h, 100L / h, 200L / h, 300L / h, 400L / h, 500L / h, 550L / h, or any value within a range of 80L / h to 550L / h, and in the second reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 150L / h, 200L / h, 300L / h, 400L / h, In the third reaction and the fourth reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is 150 L / h, 200 L / h, 300 L / h, 400 L / h, 500 L / h, 600 L / h, 700 L / h, 750 L / h, or any value within the range of 150 L / h to 750 L / h.

[0080] In one alternative embodiment, the flow rate of the nickel-cobalt-manganese ternary mixed solution is increased stepwise in each of the first reaction, the second reaction, the third reaction, and the fourth reaction.

[0081] The four-layer structure of the ternary positive electrode material precursor is formed as follows. The products from the first and second steps are used as seed crystals to carry out further reactions, and the flow rate of the ternary metal is gradually increased in each step, forming a multi-layered yet porous internal structure. The conditions for the fourth reaction are then adjusted to form a shell layer with a dense structure. The porosity of the internal structure of the ternary positive electrode material precursor granules is determined by the pH adjustment, ammonia concentration, and the rate of increase in the flow rate of the raw material ternary mixed metal salt solution in each of the above steps.

[0082] In an alternative embodiment, the stepwise increase is from 10% to 100%.

[0083] Optionally, the incremental increase is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any value in the range of 10% to 100%.

[0084] In an alternative embodiment, the pH of the system gradually decreases in the first reaction, the second reaction and the third reaction, and the pH of the system in the fourth reaction is higher than that in the third reaction.

[0085] In one alternative embodiment, the pH range of the system in the first reaction, the second reaction, the third reaction, and the fourth reaction is 10 to 12.

[0086] In one alternative embodiment, the pH of the system in the fourth reaction is 0.10 to 0.30 higher than that of the system in the third reaction.

[0087] Optionally, in said fourth reaction, the pH of the system is higher than that of the third reaction by 0.1, 0.2, 0.3, or any value within the range of 0.10 to 0.30.

[0088] By adjusting the increasing rate of the flow rate and pH of the raw material metal salt mixed solution, the products from the second and third steps can be grown quickly in a short period of time, and the porosity of the inner part and the average thickness of each layer are determined by the reaction time, pH, and increasing rate of the flow rate of the raw material metal salt mixed solution in each of the above steps.

[0089] In one alternative embodiment, the nickel-cobalt-manganese ternary mixed solution has a concentration of 90 to 130 g / L.

[0090] Optionally, the concentration of the nickel-cobalt-manganese ternary mixed solution is 90 g / L, 100 g / L, 110 g / L, 120 g / L, 125 g / L, 130 g / L, or any value within the range of 90 to 130 g / L.

[0091] In one alternative embodiment, the complexing agent comprises one or more of aqueous ammonia, EDTA, ethylenediamine, sodium citrate, and urea.

[0092] In one alternative embodiment, the complexing agent is aqueous ammonia having a mass fraction of 15% to 35%.

[0093] Optionally, the mass fraction of aqueous ammonia is 15%, 20%, 25%, 30%, 35%, or any value within the range of 15% to 35%.

[0094] In one alternative embodiment, in the first reaction, the second reaction, the third reaction, and the fourth reaction, the concentration of the aqueous ammonia in the system is 2.5 g / L to 6.5 g / L.

[0095] Optionally, in the first reaction, the second reaction, the third reaction, and the fourth reaction, the concentration of the aqueous ammonia in the system is 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L, 6.0 g / L, 6.5 g / L, or any value within a range of 2.5 g / L to 6.5 g / L.

[0096] In one alternative embodiment, the concentration of ammonia water in the system in the third and fourth reactions is 1.0 to 3.0 g / L higher than the concentration of ammonia water in the second reaction.

[0097] Optionally, in the third and fourth reactions, the concentration of the aqueous ammonia in the system is higher than the concentration of the aqueous ammonia in the second reaction by 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, 3.0 g / L, or any value within a range of 1.0 to 3.0 g / L.

[0098] In one alternative embodiment, the pH adjuster comprises one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate.

[0099] In one alternative embodiment, the pH adjuster is an aqueous sodium hydroxide solution having a mass fraction of 25% to 50%.

[0100] Optionally, the mass fraction of the aqueous sodium hydroxide solution is 25%, 30%, 35%, 40%, 45%, 50%, or any value within the range of 25% to 50%.

[0101] The present application further provides a ternary positive electrode material, which includes, from inside to outside, an A layer, a B layer, a C layer, and a D layer, the A layer, the B layer, and the C layer having increasing porosity, and the D layer having the smallest porosity or being a non-porous layer.

[0102] In an alternative embodiment, the ternary positive electrode material is prepared by sintering the ternary positive electrode material precursor described above.

[0103] For example, a lithium source compound and the above-mentioned ternary positive electrode material precursor are used as raw materials and sintered to prepare a ternary positive electrode material.

[0104] The present application further provides a lithium-ion battery cathode comprising the above-mentioned ternary cathode material.

[0105] The present application further provides a lithium-ion battery comprising the above-described lithium-ion battery positive electrode.

[0106] The present application further provides an electrical device comprising the above-mentioned lithium ion battery.

[0107] The technical solution of the present application will be described in detail below with specific examples. Those skilled in the art will understand that the following examples are merely for the purpose of illustrating the present application, and do not limit the scope of the present application. In the examples, the specific conditions are not specified, and the test can be performed under conventional conditions or conditions recommended by the manufacturer. For reagents or equipment used that are not specified by manufacturer, conventional products available on the market can be used.

[0108] Example 1 In this embodiment, a high nickel ternary precursor material for a positive electrode active material having a four-layer structure (core, two intermediate layers, shell) with a porous interior and a dense shell layer was prepared, and the chemical formula was Ni 0.85 Co 0.10 Mn 0.05We synthesized a substance called (OH)2.

[0109] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.85:0.10:0.05 were prepared into a ternary mixed metal salt solution having a concentration of 100 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used. 2. First step of preparing core A by coprecipitation: Add 5.0 ml of 1# reaction kettle. 3 Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda (sodium hydroxide aqueous solution), so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped. 3. Second step of forming a porous second intermediate layer structure B by coprecipitation: 1.8 ml of the slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3The stirring speed was set to 220 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was set to 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, aqueous ammonia solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h and the flow rate of the ternary metal at the end was 450 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dried material. 4. The third step of forming the porous third intermediate layer C: 5.5 m 3 100 kg of pure water was added, and 75 kg of the dehydrated and dried material from the second step was added. Under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was 5.5 g / L, the temperature was raised to 60 °C, and the ternary mixed solution, ammonia water solution and sodium hydroxide solution were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metals was increased stepwise, the flow rate of the ternary metals at the start was 200 L / h, and the flow rate of the ternary metals at the end was 520 L / h. The pH at the start was 10.50. 5. The fourth step to form a dense shell D: Based on the reaction conditions of the third step, the stirring speed was reduced and the pH was increased so that the stirring rotation speed of the final stage reaction was 60 r / min and the final pH was 10.65. Reducing the stirring intensity and the supersaturation of the solution in the fourth reaction can contribute to the growth of crystals at the interface, and increasing the pH of the system in the fourth reaction can contribute to the stabilization of the strength of the crystal granules, thus forming a dense shell structure. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 13.0-14.0 μm, the supply of the material was stopped. 6. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400ppm and less than 3000ppm, respectively, and the washed solid granular product is dried in a temperature environment of 100℃ for 24 hours, sieved through a 400 mesh sieve, packaged and sealed. In this way, a high-nickel ternary precursor material of a positive electrode material active material with a four-layer structure of a porous interior and a dense shell layer is obtained.

[0110] Example 2 In this embodiment, a high nickel ternary precursor material for a positive electrode active material having a four-layer structure (core, two intermediate layers, shell) with a porous interior and a dense shell layer was prepared, and the chemical formula was Ni 0.80 Co 0.10 Mn 0.10 We synthesized a substance called (OH)2.

[0111] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.80:0.10:0.10 were prepared into a ternary mixed metal salt solution with a concentration of 105 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used. 2. First step of preparing core A by coprecipitation: Add 5.0 ml of 1# reaction kettle. 3Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped. 3. Second step of forming a porous second intermediate layer structure B by coprecipitation: 1.8 ml of the slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3 The stirring speed was set to 220 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was set to 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 480 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dry material. 4. The third step of forming the porous third intermediate layer C: 5.5 m 3100 kg of pure water was added, and 80 kg of the dehydrated and dried material from the second step was added. Under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 5.5 g / L, the temperature was raised to 60 °C, and the ternary mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metals was increased stepwise, and the flow rate of the ternary metals at the start was 200 L / h, and the flow rate of the ternary metals at the end was 550 L / h. The pH at the start was 10.55. 5. The fourth step to form a dense shell D: Based on the reaction conditions of the third step, the stirring speed was lowered and the pH was raised so that the stirring rotation speed of the final stage reaction was 60 r / min and the final pH was 10.70. By lowering the stirring intensity and the degree of supersaturation of the solution in the fourth reaction, it can contribute to the growth at the interface of the crystals, and by raising the pH of the system in the fourth reaction, it can contribute to the stabilization of the strength of the crystal granules, and therefore a dense shell structure is formed. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 13.0-14.0 μm, the supply of the material was stopped. 6. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400ppm and less than 3000ppm, respectively, and the washed solid granular product is dried in a temperature environment of 100°C for 24 hours, sieved through a 400 mesh sieve, packaged and sealed. In this way, a high-nickel ternary precursor material of a positive electrode material active material with a four-layer structure of a porous interior and a dense shell layer is obtained.

[0112] Example 3 In this embodiment, a high nickel ternary precursor material for a positive electrode active material having a four-layer structure (core, two intermediate layers, shell) with a porous interior and a dense shell layer was prepared, and the chemical formula was Ni 0.90 Co 0.05 Mn 0.05 We synthesized a substance called (OH)2.

[0113] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.90:0.05:0.05 were prepared into a ternary mixed metal salt solution with a concentration of 110 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used. 2. First step of preparing core A by coprecipitation: Add 5.0 ml of 1# reaction kettle. 3 Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped. 3. Second step of forming a porous second intermediate layer structure B by coprecipitation: 1.8 ml of the slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3The stirring speed was set to 220 r / min, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, aqueous ammonia solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 500 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dried material. 4. The third step of forming the porous third intermediate layer C: 5.5 m 3 100 kg of pure water was added, and 85 kg of the dehydrated and dried material from the second step was added. Under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 5.5 g / L, the temperature was raised to 60 °C, and the ternary mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metals was increased stepwise, and the flow rate of the ternary metals at the start was 200 L / h, and the flow rate of the ternary metals at the end was 600 L / h. The pH at the start was 10.60. 5. The fourth step to form a dense shell D: Based on the reaction conditions of the third step, the stirring speed was reduced and the pH was increased so that the stirring rotation speed of the final stage reaction was 60 r / min and the final pH was 10.75. Reducing the stirring intensity and the supersaturation of the solution in the fourth reaction can contribute to the growth of crystals at the interface, and increasing the pH of the system in the fourth reaction can contribute to the stabilization of the strength of the crystal granules, thus forming a dense shell structure. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 13.0-14.0 μm, the supply of the material was stopped. 6. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400ppm and less than 3000ppm, respectively, and the washed solid granular product is dried in a temperature environment of 100°C for 24 hours, sieved through a 400 mesh sieve, packaged and sealed. In this way, a high-nickel ternary precursor material of a positive electrode active material having a four-layer structure with a porous interior and a dense shell layer is obtained.

[0114] Example 4 In this embodiment, a high nickel ternary precursor material for a positive electrode active material having a four-layer structure (core, two intermediate layers, shell) with a porous interior and a dense shell layer was prepared, and the chemical formula was Ni 0.93 Co 0.04 Mn 0.03 We synthesized a substance called (OH)2.

[0115] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.93:0.04:0.03 were prepared into a ternary mixed metal salt solution having a concentration of 125 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used. 2. First step of preparing core A by coprecipitation: Add 5.0 ml of 1# reaction kettle. 3Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped. 3. Second step of forming a porous second intermediate layer structure B by coprecipitation: 1.8 ml of the slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3 The stirring speed was set to 220 r / min, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, aqueous ammonia solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 550 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dry material. 4. The third step of forming the porous third intermediate layer C: 5.5 m 3100 kg of pure water was added, and 90 kg of the dehydrated and dried material from the second step was added. Under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 5.5 g / L, the temperature was raised to 60 °C, and the ternary mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metals was increased stepwise, and the flow rate of the ternary metals at the start was 200 L / h, and the flow rate of the ternary metals at the end was 650 L / h. The pH at the start was 10.65. 5. The fourth step to form a dense shell D: Based on the reaction conditions of the third step, the stirring speed was reduced and the pH was increased so that the stirring rotation speed of the final stage reaction was 60 r / min and the final pH was 10.85. Reducing the stirring intensity and the supersaturation of the solution in the fourth reaction can contribute to the growth of crystals at the interface, and increasing the pH of the system in the fourth reaction can contribute to the stabilization of the strength of the crystal granules, thus forming a dense shell structure. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 13.0-14.0 μm, the supply of the material was stopped. 6. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400ppm and less than 3000ppm, respectively, and the washed solid granular product is dried in a temperature environment of 100°C for 24 hours, sieved through a 400 mesh sieve, packaged and sealed. In this way, a high-nickel ternary precursor material of a positive electrode active material having a four-layer structure with a porous interior and a dense shell layer is obtained.

[0116] Comparative Example 1 In this comparative example, a high nickel ternary precursor material for a positive electrode active material having a three-layer structure (core, intermediate layer, shell) with few internal pores and a dense shell layer was prepared, and the chemical formula was Ni 0.85 Co 0.10 Mn 0.05 We synthesized a substance called (OH)2.

[0117] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.85:0.10:0.05 were prepared into a ternary mixed metal salt solution with a concentration of 110 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used. 2. First step: Add 5.0m to 1# reactor. 3 Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped. 3. Second step: 1.8m of slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3The stirring speed was set to 220 r / min, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, aqueous ammonia solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 500 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dried material. 4. Third step: Add 5.5m to 3# reactor 3 100 kg of pure water was added, 75 kg of the dehydrated and dried material from the second step was added, and under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was 7.5 g / L, the temperature was raised to 60 ° C, and the ternary mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 500 L / h. The pH at the start was 10.45, the pH at the end was 10.60, and the stirring rotation speed of the reaction at the end stage was gradually lowered to 60 r / min. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged, and when the particle size D50 of the slurry material reached 13.0-14.0 μm, the material supply was stopped. 5. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400 ppm and less than 3000 ppm, respectively. The washed solid granular product is dried in a temperature environment of 100°C for 24 hours, sieved through a 400 mesh sieve, packaged and sealed.

[0118] In Comparative Example 1, the steps and the flow rate of the ternary metal were almost the same as those in the Example, and a ternary precursor material having a dense three-layer structure was obtained by adjusting the final pH and ammonia water concentration in the Comparative Example.

[0119] Comparative Example 2 In this comparative example, a high nickel ternary precursor material for a positive electrode active material having a two-layer structure (core, shell) with few internal pores and a dense shell layer was prepared, and the chemical formula was Ni 0.80 Co 0.15 Mn 0.05 We synthesized a substance called (OH)2.

[0120] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.80:0.15:0.05 were prepared into a ternary mixed metal salt solution with a concentration of 110 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used.

[0121] 2. First step: Add 5.0m to 1# reactor. 3Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 2.0-3.0μm, the material supply was stopped.

[0122] 3. Second step: 1.8m of slurry material from the first step 3 Transfer to 2# reactor and add 5.0m of pure water. 3 The stirring speed was set to 220 r / min, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 4.0 g / L, the pH was set to 11.00, the temperature was raised to 60 ° C, and the ternary metal mixed solution, aqueous ammonia solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 500 L / h. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 3.0 to 5.0 μm, the material supply was stopped. Dehydration was performed to obtain a dried material.

[0123] 4. Third step: Add 5.0m to the 3# reactor. 3100 kg of pure water was added, 75 kg of the dehydrated and dried material from the second step was added, and under stirring conditions of 180 r / min, ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was 8.0 g / L, the temperature was raised to 60 ° C, and the ternary mixed solution, ammonia aqueous solution and sodium hydroxide solution were simultaneously introduced to carry out a coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, the flow rate of the ternary metal at the start was 200 L / h, and the flow rate of the ternary metal at the end was 500 L / h. The pH at the start was 10.40, the pH at the end was 10.55, and the stirring rotation speed of the reaction at the end stage was gradually lowered to 60 r / min. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged, and when the particle size D50 of the slurry material reached 13.0-14.0 μm, the material supply was stopped.

[0124] 5. Post-treatment: After the reaction is stopped, the product is washed with an appropriate amount of dilute alkali and pure water until the Na content and S content in the product are less than 400 ppm and less than 3000 ppm, respectively. The washed solid granular product is dried in a temperature environment of 100°C for 24 hours, sieved through a 400 mesh sieve, packaged and sealed.

[0125] In Comparative Example 2, the steps and the flow rate of the ternary metal were almost the same as those in the Example, and by adjusting the pH and the ammonia water concentration at the end of the comparative example, a ternary precursor material having a two-layer structure with a dense interior and few pores was obtained.

[0126] Comparative Example 3 In this comparative example, a high nickel ternary precursor material for the positive electrode active material having a dense internal structure (core, shell) was prepared in two steps, and the chemical formula was Ni 0.85 Co 0.10 Mn 0.05 We synthesized a substance called (OH)2.

[0127] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.85:0.10:0.05 were prepared into a ternary mixed metal salt solution with a concentration of 110 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used.

[0128] 2. First step: Add 8.0m to 1# reactor. 3 Pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 11.90, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were introduced simultaneously to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, and the flow rate of the ternary metal at the start was 100L / h, and the flow rate of the ternary metal at the end was 500L / h. The pH at the end was adjusted to 11.20. When the liquid level in the reaction vessel reached the specified level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged, and when the particle size D50 of the slurry material reached 3.0-5.0μm, the material supply was stopped.

[0129] 3. Second step: Dehydration and drying of the slurry material from the first step: 80 kg of the material is placed in a 2# reactor and 5.0 m of pure water is poured into it. 3The stirring speed was set to 220r / min, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, so that the ammonia concentration of the system was 6.0g / L, the pH was 10.80, the temperature was raised to 60°C, and the ternary metal mixed solution, ammonia water solution and sodium hydroxide solution were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metal was increased stepwise, the flow rate of the ternary metal at the start was 200L / h, and the flow rate of the ternary metal at the end was 600L / h. During the reaction process, the stirring speed was gradually reduced, the rotation speed at the end stage was 100r / min, the pH of the reaction system was gradually increased, and the pH at the end was 11.20. When the liquid level in the reaction vessel reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 12.0 to 14.0 μm, the supply of the material was stopped.

[0130] In Comparative Example 3, the pH of the system was gradually increased in the second step, and the final pH was 11.20, which was almost the same as the final pH in the first step, and thus a ternary precursor material having a dense internal structure (core, shell) was obtained. A ternary precursor material having a four-layer structure with a porous interior and a dense shell as in the Example could not be obtained.

[0131] Comparative Example 4 In this comparative example, a ternary precursor material of a positive electrode active material having a low nickel content (5 series), dense internal structure, non-porous and non-lamellar structure, and the chemical formula is Ni 0.50 Co 0.20 Mn 0.30 We synthesized a substance called (OH)2.

[0132] The preparation method included the following steps: 1. Material selection: Nickel(II) sulfate (NiSO4·6H2O), cobalt(II) sulfate (CoSO4·7H2O) and manganese(II) sulfate (MnSO4·H2O) were used. Metal raw materials containing nickel, cobalt and manganese in a molar ratio of 0.50:0.20:0.30 were prepared into a ternary mixed metal salt solution with a concentration of 110 g / L. A liquid caustic soda with a mass fraction of 32% and an aqueous ammonia solution with a mass fraction of 20% were used, and the 3 Stainless steel reactor, 1.3m 3 A stainless steel concentrator was used.

[0133] 2. First step: Add 8.0m to 1# reactor. 3 The pure water was added as the base solution, and ammonia concentration and pH were adjusted by adding ammonia water and liquid caustic soda, so that the ammonia concentration of the system was 4.0g / L, the pH was 10.95, the reaction temperature was raised to 60℃, the stirring speed was set to 220r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were simultaneously introduced to carry out the coprecipitation reaction. The flow rate of the ternary metal was 500L / h, the flow rate of the liquid caustic soda was 185L / h, and the flow rate of the ammonia water was 17L / h. When the liquid level in the reaction vessel reached a predetermined level, the mother liquor was discharged, and the concentration of the product increased accordingly. When the particle size D50 of the slurry material was stably contained at 7.0-9.0μm, the supply of materials to the reaction system was stopped.

[0134] 3. Second step: 7.5m of slurry material from the first step 3 The mixture was transferred to the 2# reaction kettle, and ammonia water and liquid caustic soda were added to adjust the ammonia concentration and pH, the ammonia concentration of the system was set to 5.0g / L, the pH to 10.80, the reaction temperature was raised to 60°C, the stirring rotation speed was set to 200r / min, and after the required conditions were met, the nickel-cobalt-manganese ternary metal mixed solution, liquid caustic soda and ammonia water were simultaneously introduced to carry out the coprecipitation reaction. During the reaction process, the flow rate of the ternary metal, the stirring rotation speed and the pH were kept constant. When the liquid level in the reaction kettle reached a predetermined level, the concentrator was started, the slurry material was circulated, and the mother liquor was discharged. When the particle size D50 of the slurry material reached 10.0-13.0μm, the material supply was stopped.

[0135] The low nickel series products according to Comparative Example 4 were carried out in two steps compared to the examples, with stirring at a high rotation speed, constant flow rate and pH, and obtained a dense, non-porous and non-stratified structure inside. The ternary precursor material with a porous interior and dense shell four-layer structure according to the examples could not be obtained.

[0136] The precursors according to the examples and the comparative examples were tested, and the test results are shown in FIGS. Specifically, FIG. 2 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Example 1, FIG. 3 is a high-magnification scanning electron microscope photograph of the ternary positive electrode material precursor obtained in Example 1, FIG. 4 is a high-magnification scanning electron microscope photograph showing a part of the ternary positive electrode material precursor obtained in Example 1, FIG. 5 is a high-magnification scanning electron microscope photograph of the ternary positive electrode material precursor obtained in Example 2, FIG. 6 is a high-magnification scanning electron microscope photograph showing a part of the ternary positive electrode material precursor obtained in Example 2, FIG. 7 is an XRD spectrum of the ternary positive electrode material precursors obtained in Examples 1, 2, 3, and 4 (the figures show, from top to bottom, those according to Examples 3, 4, 2, and 1), FIG. 8 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Example 2, and FIG. 9 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Example 3. 10 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Example 4, FIG. 11 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Comparative Example 1, FIG. 12 is a high-magnification scanning electron microscope photograph of the ternary positive electrode material precursor obtained in Comparative Example 1, FIG. 13 is a high-magnification scanning electron microscope photograph showing a portion of the ternary positive electrode material precursor obtained in Comparative Example 1, FIG. 14 is an XRD spectrum of the ternary positive electrode material precursor obtained in Comparative Example 1, FIG. 15 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Comparative Example 2, FIG. 16 is an XRD spectrum of the ternary positive electrode material precursor obtained in Comparative Example 2, FIG. 17 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Comparative Example 3, FIG. 18 is an XRD spectrum of the ternary positive electrode material precursor obtained in Comparative Example 3, and FIG. 19 is an SEM photograph of a cross section of the ternary positive electrode material precursor obtained in Comparative Example 4.

[0137] From Figures 2, 8, 9 and 10, it was confirmed that the ternary precursor obtained in the examples had a four-layer structure including a core, two intermediate layers and a shell, and that the inside was porous and the shell layer was dense with few pores.

[0138] From FIG. 11, it was confirmed that the precursor obtained in Comparative Example 1 had a three-layer structure including a core, one intermediate layer, and a shell, and that all layers from the inside to the shell layer were dense and had few pores.

[0139] 15 and 17, it was confirmed that the precursors obtained in Comparative Example 2 and Comparative Example 3, respectively, had a two-layer structure including a core and a shell, and that both were dense and had few pores from the inside to the shell layer.

[0140] From FIG. 19, it could be confirmed that the precursor obtained in Comparative Example 4 (low nickel) was dense from the inside to the shell layer, had few pores, and had a non-stratified structure.

[0141] The performance parameters of the ternary positive electrode material precursors obtained in each of the examples and comparative examples are shown in Table 1.

[0142] [Table 1]

[0143] 2000g of the precursor prepared in the example was mixed uniformly with LiOH·H2O in a molar ratio of 1:1.03 using a high-speed mixer, and sintered in a box furnace under air at a sintering temperature of 780℃. The mixture was sintered in a high-temperature environment for 12 hours, cooled to room temperature, and then crushed and sieved to obtain a nickel-cobalt-manganese ternary single crystal positive electrode material.

[0144] Electrochemical performance evaluation was performed using a half coin cell. The above positive electrode material, conductive carbon black, and adhesive PVDF (polyvinylidene fluoride) were made into a slurry in a ratio of 8:1:1, and applied to aluminum foil to produce a positive electrode plate. A metallic lithium plate was used as the negative electrode plate, and 1 mol / L LiPF6 / EC:DMC (volume ratio was 1:1) was used as the electrolyte. In a vacuum glove box, a battery case, positive electrode plate, negative electrode plate, separator, elastic piece, and gasket were assembled to form a coin cell. Electrochemical performance evaluation was performed using the LAND evaluation system.

[0145] The battery was evaluated by charging and discharging it at 1C for 50 cycles under conditions of 3.0 to 4.3 V in a room temperature environment. The electrochemical performance is shown in Table 2.

[0146] [Table 2]

[0147] From Table 1, it can be seen that, compared to Comparative Examples 1, 2, and 3, the ternary precursor granules of Examples 1, 2, 3, and 4 have a stable 4-layer structure with a porous interior and a dense shell, rather than a dense 2- or 3-layer structure, and Comparative Example 4 (low nickel) has a dense structure without stratification. The ternary precursors of the Examples have a stable structure with multiple interior layers and a dense shell, have a larger porosity than the Comparative Examples, are less likely to crack during charging and discharging, and have better structural stability and electrochemical performance of the product granules.

[0148] From Table 1, it can be seen that, compared to Comparative Example 3 and Comparative Example 4, Examples 1, 2, 3, and 4 have a particle size distribution width within the range of 1.20±0.05, and thus have a narrower particle size distribution and a more uniform distribution.

[0149] From Table 1, it can be seen that the 001 peak half width of the embodiment is smaller than that of the comparative example, the FWHM ratio (101 / 001) is 1.1-1.2 in the embodiment, and I(001 / 101) is 1.1-1.2 in the embodiment, so that the 001 peak half width is smaller than the 101 peak half width and the 001 peak intensity is higher than the 101 peak intensity by XRD diffraction, that is, the material according to the embodiment grows preferentially at the 001 peak, has stronger crystallinity, and has a more stable structure. In the case of Comparative Example 4 (low nickel product), Comparative Example 4 is a material with a low nickel, high cobalt, and high manganese ratio, and the difference in ratio between the low nickel and high nickel products is too large, so they are not compared. From Table 2 on electrochemical performance, it can be confirmed that the electrochemical performance of the high nickel product is better.

[0150] From the electrochemical performance in Table 2, it can be seen that in the examples, the rate performance reached 93.45% to 95.18%, which was improved by 2.49% to 6.19%, and the capacity retention rate after cycling reached 97.75% to 98.63%, which was improved by 5.19% to 7.70%, compared to Comparative Examples 1, 2, 3, and 4.

[0151] Therefore, the ternary positive electrode material high nickel based precursor according to the present application has better performance.

[0152] The four-layer structure inside the granules of the ternary positive electrode material precursor material according to the present application differs from the conventional dense structure in that it has a stable multilayered and porous structure, pointing a new direction in research into the multilayered structure inside the granules of ternary positive electrode material precursors.

[0153] The above embodiments are merely for illustrating the technical solution of the present application, and are not intended to limit it. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art may modify the technical solutions described in the above embodiments, and may make equivalent substitutions for some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solution to depart from the scope of the technical solution of each embodiment of the present application. In addition, some embodiments have some features included in other embodiments, but the combination of features of different embodiments is also another embodiment within the scope of the present application. For example, the embodiments to be protected in the claims may be arbitrarily combined. The information disclosed in the background section is intended to deepen the understanding of the entire background technology of the present application, and is not intended to acknowledge or imply in any way that it is a prior art known to those skilled in the art.

Claims

1. The core layer, the first intermediate layer, the second intermediate layer, and the shell layer are included in this order from inside to outside, and the porosity of the core layer, the first intermediate layer, and the second intermediate layer increases in this order, and the shell layer is the layer with the smallest porosity or is a non-porous layer. A ternary positive electrode material precursor comprising:

2. The porosity of the core layer is 1.40% to 7.96%, the porosity of the first intermediate layer is 2.10% to 8.37%, the porosity of the second intermediate layer is 4.57% to 16.72%, and the porosity of the shell layer is 1% or less. The ternary positive electrode material precursor of claim 1.

3. The porosity of the core layer is 2.0% to 4.0%, the porosity of the first intermediate layer is 3.0% to 5.0%, the porosity of the second intermediate layer is 7.35% to 10.32%, and the porosity of the shell layer is 0.5% or less. The ternary positive electrode material precursor of claim 1.

4. The average thickness of each layer is 3 μm or less. The ternary positive electrode material precursor of claim 1.

5. The diameter of the core layer is 1.0 μm to 3.0 μm, the average thickness of the first intermediate layer is 0.2 μm to 2.0 μm, the average thickness of the second intermediate layer is 1 μm to 2.5 μm, and the average thickness of the shell layer is 0.5 μm to 1.5 μm. The ternary positive electrode material precursor of claim 1.

6. the primary granules in the ternary positive electrode material precursor are distributed in a sparse, intersecting needle shape from the inside to the outside along a radial direction of the ternary positive electrode material precursor, The core layer has a spherical shape as a whole, The primary granules in the shell layer are needle-shaped along the radial direction of the ternary positive electrode material precursor. The ternary positive electrode material precursor of claim 1.

7. The average particle size of the ternary positive electrode material precursor is 12 μm to 15 μm. The ternary positive electrode material precursor of claim 1.

8. D95 / D50=1.0 to 1.6 The ternary positive electrode material precursor of claim 1.

9. The BET specific surface area of ​​the ternary positive electrode material precursor is 11 m 2 / g to 17 m 2 / g. The ternary positive electrode material precursor of claim 1.

10. The general formula is Ni x Co y Mn z (OH) 2 where 0.8≦x≦0.98, 0.01≦y<0.18, 0.01≦z<0.17, and x+y+z=1 are satisfied. The ternary positive electrode material precursor according to any one of claims 1 to 9.

11. A method for preparing a ternary positive electrode material precursor according to any one of claims 1 to 9, comprising the steps of: A step of performing a first reaction on a raw material including a nickel-cobalt-manganese ternary mixed solution, a complexing agent, and a pH adjuster to obtain a core layer; adjusting reaction conditions to carry out a second reaction to form a first intermediate layer on the surface of the core layer; adjusting reaction conditions to carry out a third reaction to form a second intermediate layer on the surface of the first intermediate layer; and adjusting reaction conditions to carry out a fourth reaction to form a shell layer on the surface of the second intermediate layer; In each of the first reaction, the second reaction, the third reaction, and the fourth reaction, the flow rate of the nickel-cobalt-manganese ternary mixed solution is increased stepwise; In the first reaction, the second reaction, the third reaction, and the fourth reaction, the pH range of the system is 10 to 12; In the first reaction, the second reaction and the third reaction, the pH of the system gradually decreases, and in the fourth reaction, the pH of the system is higher than that of the third reaction; In the first reaction, the second reaction, the third reaction, and the fourth reaction, the complexing agent contains ammonia water, and the concentration of the ammonia water in the system is 2.5 g / L to 6.5 g / L; In the third and fourth reactions, the concentration of the aqueous ammonia in the system is 1.0 to 3.0 g / L higher than the concentration of the aqueous ammonia in the second reaction. A method for preparing a ternary positive electrode material precursor comprising:

12. The first reaction, the second reaction, the third reaction, and the fourth reaction are all carried out under stirring, and the stirring speed is sequentially decreased. The stirring speed of the first reaction is 200 r / min to 240 r / min, the stirring speed of the second reaction is 180 r / min to 230 r / min, the stirring speed of the third reaction is 100 r / min to 200 r / min, and the stirring speed of the fourth reaction is 40 r / min to 100 r / min. The preparation method according to claim 11.

13. In the first reaction, the addition flow rate of the nickel-cobalt-manganese ternary mixed solution is 80 L / h to 550 L / h, in the second reaction, the addition flow rate of the nickel-cobalt-manganese ternary mixed solution is 150 L / h to 650 L / h, in the third reaction and the fourth reaction, the addition flow rate of the nickel-cobalt-manganese ternary mixed solution is 150 L / h to 750 L / h, The stepwise increase is from 10% to 100%. The preparation method according to claim 11.

14. In the fourth reaction, the pH of the system is 0.10 to 0.30 higher than that of the third reaction. The preparation method according to claim 11.

15. The concentration of the nickel-cobalt-manganese ternary mixed solution is 90 to 130 g / L; the complexing agent is aqueous ammonia having a mass fraction of 15% to 35%; The pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate; The pH adjuster is an aqueous solution of sodium hydroxide having a mass fraction of 25% to 50%. The preparation method according to claim 11.

16. A ternary positive electrode material, The laminated structure includes, from inside to outside, an A layer, a B layer, a C layer, and a D layer, the A layer, the B layer, and the C layer having increasing porosity in this order, and the D layer having the smallest porosity or being a non-porous layer. A ternary positive electrode material characterized by:

17. The ternary positive electrode material according to claim 16 is included. A lithium ion battery positive electrode comprising:

18. The lithium ion battery positive electrode of claim 17 is included. A lithium-ion battery characterized by:

19. The lithium ion battery according to claim 18 is provided.

1. An electrical installation comprising:

Citation Information

Patent Citations

  • Positive electrode active material precursor, preparation method thereof, and positive electrode active material

    CN111653756A

  • Nickel-cobalt-manganese ternary material, precursor thereof, preparation method of precursor, and application of material

    CN112928250A

  • Nickel-cobalt hydroxide and preparation method thereof, nickel-cobalt oxide, lithium ion battery positive electrode material, positive electrode, battery and electric equipment

    CN114261997A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery arranged by use thereof

    JP2015072800A

  • Nickel-based active material precursor for lithium secondary battery, method for producing the same, nickel-based active material formed therefrom for lithium secondary battery, and lithium secondary battery including positive electrode including the same

    JP2020064858A